Pengaturan Rasio Zat Penjernih Air menggunakan PLC (Programmable Logic Controller) pada Water Treatment di Pusat Pengembangan Sumber Daya Manusia Minyak dan Gas Bumi (PPSDM MIGAS) CEPU - Pamungkas, Dimas Irfan Putra Firman; Stighfarrinata, Rizky (Jurnal Teknologi dan Manajemen Sistem Industri, 2022)
PPSDM Migas Cepu is one of the industries engaged in Human Resource Development in the Oil and Gas sector. Based on the Regulation of the Minister of Energy and Mineral Resources Number 13 of 2016, concerning the Organization and Work Procedures of the Ministry of Energy and Mineral Resources, the organizational structure of the Oil and Gas PPSDM is divided into 3 areas, namely the planning and standardization field, the program and evaluation field and the implementation and infrastructure sector as well as from the administrative side assisted by the administrative section. . In the water treatment plant, PLC is used for control. The purpose of waste treatment is to prevent and overcome pollution and/or environmental damage caused by B3 waste and to restore the quality of the polluted environment so that it is in accordance with its function. Waste is waste whose presence at a certain time and place is not desired by the environment because it has no economic value. Waste contains contaminants that are toxic and dangerous. This waste is known as B3 waste (toxic and hazardous materials). This material is formulated as a material in relatively small quantities but has the potential to pollute/damage the environment and resources. From the results of the research conducted, it is found that the control system with a fast process using the Proportional + Integral (PI) controller mode is preferred considering that the system response is more stable to reach the setpoint. Also, if using HMI can make it easier to observe the simulation, when the on button is pressed, the system will run and the tank of substances will start to decrease. The decrease in the value of the substance tank is influenced by the mixing value, and in the above simulation, the working Dukem substance tank is shown in the red simulation pipe.